2011
DOI: 10.1002/chem.201002779
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Electronic versus Steric Effects in Stereoselective Ring‐Opening Polymerization of Lactide and β‐Butyrolactone with Amino‐alkoxy‐bis(phenolate)–Yttrium Complexes

Abstract: A series of methoxy-amino-bis(phenol)s (ONOO(R(1),R(2)))H(2) possessing on the phenol rings R(1) ortho substituents with variable steric and electronic properties (R(1)=CMe(2)Ph, 1; CMe(2)tBu, 3; CMe(2)(4-CF(3)C(6)H(4)), 5; CPh(3), 9; Cl, 10) has been synthesized and further reacted with [Y{N(SiHMe(2))(2)}(3)](THF)(2) to give cleanly the corresponding yttrium compounds [Y(ONOO(R(1),R(2))){N(SiHMe(2))(2)}(thf)(n)] (Y-x); the solid-state structures of Y-3 and Y-10 have been determined. These amido complexes have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
133
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(146 citation statements)
references
References 58 publications
8
133
0
Order By: Relevance
“…This observation is consistent with those of Carpentier and co-workers. 21 Greater activities of Zn(II) initiators 1 and 3 in comparison to the Cu(II) catalysts 2 and 4 agree with literature reports. 22 We also observed some influence of monomer stereochemistry on the kinetics of the polymerization reactions.…”
Section: Methodssupporting
confidence: 87%
“…This observation is consistent with those of Carpentier and co-workers. 21 Greater activities of Zn(II) initiators 1 and 3 in comparison to the Cu(II) catalysts 2 and 4 agree with literature reports. 22 We also observed some influence of monomer stereochemistry on the kinetics of the polymerization reactions.…”
Section: Methodssupporting
confidence: 87%
“…It is noteworthy that, in sharp contrast, this [Y{ON(OMe)-O Cl,Cl }(OiPr)] catalyst is essentially nonstereoselective in the ROP of rac-LA (P r = 0.56) and rac-BL (P r = 0.42−0.45). 23 Obviously, considerations different from the steric and electronic ones mentioned above for the ROP of rac-LA and rac-BL are at work in the ROP of of β-malolactonates. However, their exact nature still remains unknown; it is unclear if this might be related to the dinuclear nature of this peculiar catalyst precursor.…”
Section: ■ Introductionmentioning
confidence: 98%
“…DFT computations performed on putative intermediates indeed indicated that such interactions may stabilize the active species by 5−10 kcal mol −1 and freeze the growing macromolecular chain in a specific conformation, enhancing stereocontrol ( Figure 2); 23 23 (b) In the NOESY 1 H− 1 H NMR spectrum of the corresponding isopropoxide species Y{ON(OMe)O CMe2Ph,CMe2Ph }(OiPr)-(THF) (generated upon alcoholysis of the former amido species), CH(OiPr)···aryl(cumyl) close contacts were also evidenced. 23 (c) Despite the fact that species of the type Y{ON(OMe)O CMe2Ph,R }(OiPr)(THF) (i.e., similar to those computed in Figure 2) could never be generated cleanly, close analogues based on tridentate ONO pyridine-bisphenolate ligands were prepared and structurally characterized; hence, in {ONO CMe2Ph,Me }Al((R)-OCH(Me)CH 2 CO 2 Me), the two cumyl substituents point in the direction of the β-alkoxybutyrate moiety, with short contacts (∼2.6−2.8 Å) between the phenyl π system and one methylene C−H of the butyrate moiety. 68 Recently, Rieger and co-workers studied the kinetics, determining the enthalpies and entropies of the ratedetermining steps through temperature-dependent in situ IR measurements and performed DFT computations on the ROP of BL initiated by the mononuclear 55 Ln{ON(OMe)O tBu2 }(N-(SiHMe 2 ) 2 )(THF) (Ln = Sm, Tb, Y, Lu).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Based on the excellent catalytic properties for lactide polymerization catalyzed by wellcharacterized rare-earth metal complexes [12][13][14][15][16], amine-bis(benzotriazole phenolate) dysprosium and yttrium complexes 1-6 are expected to behave as air-stable catalysts for ROP of lactide (LA).…”
Section: Ring-opening Polymerization Of Lactidesmentioning
confidence: 99%
“…For instance, a series of aminoalkoxybis(phenolate) yttrium complexes were developed by Carpentier and co-workers; such a yttrium amide with the bulkier ortho substituents installed on the amine-phenolate ligands was shown to be a high active initiator with great stereocontrol for producing highly heterotactic PLAs [12,13]. Recently, Yao and Shen et al…”
Section: Introductionmentioning
confidence: 97%